Architecture of Soko Wolu Traditional House in Dusun Cemorosewu - Magetan - Wahyudi, Johan; Wikantiyoso, Respati; Junianto, Junianto (University of Merdeka Malang, 2018)
Traditional houses in Indonesia have become silent witnesses of how life in the past wascarried out and its influence on the order of life of the people at that time. Likewise with thetraditional Javanese houses of the community of dusun Cemorosewu - Magetan, which havethe characteristics and functionally have specific aims and objectives that influence the processof establishing the building. This study is expected to provide a benefit in the form of thedevelopment of knowledge related to traditional houses in general which can be applied inbuilding architecture. The method used in this writing is descriptive method with non randomsampling technique, which is purposive sampling (purposive sampling technique).From the discussion, it can be seen that the traditional house in dusun Cemorosewu only hastwo clusters, namely griya wingking with dhapur limasan and griya pawon with dhapurkampong where griya pawon is always on the left either the wingking house faces north orsouth. The supporting structure of the roof of the house is supported by 8 (eight) poles so thatit is often referred to as omah soko wolu. Walls are made of split stone and zinc roofing andthere are still cooking stoves that use fuel from firewood along with complementary componentssuch as pogo and sigiran and roof openings in an effort to remove smoke.Â DOI: https://doi.org/10.26905/lw.v10i1.2660